Liikuntaintervention yhteys fyysisen aktiivisuuden lisääntymiseen ikääntyneillä - Anttilainen, Hanna (2018)
Anttilainen, H (2018). Association between physical activity intervention and increase in physical activity in older adults. University of Jyväskylä, Faculty of Sports and Health Sciences, sports and exercise medicine Master’s thesis, 33 pp., 3 appendices. Physical activity has several health benefits for older people. Despite this, the amount of physical activity decreases among older people. One can try to increase the amount of physical activity with physical activity intervention. It is still controversial which intervention types are the best to promote physical activity and how older people engage themselves in physical activity in long term. The purpose of this study was to investigate if the physical activity intervention of the PASSWORD study increases the amount of physical activity with older people. The additional purpose was also to investigate if gender, age, monthly income, subjective state of health or dizziness or feeling of loss of balance has an effect to the change in physical activity. The data was part of randomized controlled PASSWORD study. The purpose of this study is to investigate the effects of physical activity and cognitive training to walking speed and falls among physically in active older people. The data was collected from baseline questionnaires and the amount of physical activity was collected with UKK RM42 accelerometer in baseline and six-month measurement point. The data was analyzed with IBM SPSS Statistics 24 program. Independent samples t-test, paired samples t-test and repeated measures ANOVA were used to analyze the results. The amount of light physical activity increased 137 minutes and moderate physical activity 39 minutes per week. Sedentary time decreased 227 minutes per week. The difference in physical activity and sedentary time were statistically significant. Gender, age, monthly income, subjective state of health or dizziness or feeling of loss of balance did not show an association with the change in physical activity. At baseline, the participants were physically active in the light level approximately 26,4 hours per week and in the moderate level 226 minutes per week. The amount of sedentary time was 70,3 hours per week. The amount of vigorous physical activity was minimal and unequally distributed so it was not further analyzed.